Expanding Supply Chain Performance in Logistic and Forwarder Companies: How Collaboration Enhance Capabilities and Innovation Performance - I Wayan Edi Arsawan (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2023)
The changes in the business landscape between supply chains and the lack of literature on supply chains encourage scholars to investigate the relevant topic. The study aims to investigate the linkage between supply chain collaboration, capabilities, and innovation performance on supply chain performance in emerging country Indonesia. This study distributed questionnaires to 358 logistics managers and forwarders as research samples using a quantitative approach in Bali, Indonesia. The study’s results showed that supply chain collaboration significantly affected innovation performance, supply chain capabilities, and supply chain performance. In addition, innovation performance insignificant effected supply chain performance. Another crucial finding was supply chain capabilities partially mediate relationship between supply chain collaboration and supply chain performance. This result enhanced logistic and forwarder companies manager to strengthen their collaboration among partners. Theoretical and managerial implications were also discussed in this paper. Keywords: innovation performance, supply chain capabilities, supply chain collaboration, supply chain performance